Interleukin-15 and Tumor Necrosis Factor-α in Iraqi Patients with Alopecia Areata - Zainab A. Kamil; Galawish A. Abdullah; Haider Hashim Zalzala (Dermatology Research and Practice)
Background. Alopecia areata (AA) is a common form of noncicatricial hair loss of unknown cause, affecting 0.1-0.2% of the general population. Most evidence supports the hypothesis that it is disease of the hair follicle of autoimmune nature mediated by T-cells, with important cytokine role. Objective of the Study. The objective of this study is to study the association and changes in serum levels of interleukin-15 (IL-15) and tumor necrosis factor-α (TNF-α) in patients with AA in relation to the type, activity, and disease duration. Patients and Methods. Thirty-eight patients with AA and 22 individuals without the disease as controls were enrolled in this case-controlled study conducted in the Department of Dermatology in the Al-Kindy Teaching Hospital and Baghdad Medical City, Iraq, during a period from the 1st of April 2021 to the 1st of December 2021. Serum concentrations of IL-15 and TNF-α assessed using the enzyme-linked immunosorbent assay. Results. The mean serum concentration values for IL-15 and TNF-α were higher significantly in patients with AA than in controls (2.35 versus 0.35 pg/mL and 50.11 versus 20.92 pg/mL, respectively). IL-15 and TNF-α showed no statistically significant differences in level in terms of the type, duration, and activity of the disease, but TNF-α significantly higher in those with totalis-type than in other types. Conclusion. Both IL-15 and TNF-α are markers for alopecia areata. The level for these biomarkers was not affected by duration or disease activity, but it was affected by the type of disease, as the concentrations of IL-15 and TNF-α were higher in patient with Alopecia totalis than in other types of Alopecia.